Degradation of triclocarban by a triclosan-degrading Sphingomonas sp. strain YL-JM2C. (February 2016) - Mulla, Sikandar I.; Hu, Anyi; Wang, Yuwen; Sun, Qian; Huang, Shir-Ly; Wang, Han; Yu, Chang-Ping
Abstract: Bacterial degradation plays a vital role in determining the environmental fate of micropollutants like triclocarban. The mechanism of triclocarban degradation by pure bacterium is not yet explored. The purpose of this study was to identify metabolic pathway that might be involved in bacterial degradation of triclocarban. Triclosan-degrading Sphingomonas sp. strain YL-JM2C was first found to degrade up to 35% of triclocarban (4 mg L −1 ) within 5 d. Gas chromatography-mass spectrometry detected 3, 4-dichloroaniline, 4-chloroaniline and 4-chlorocatechol as the major metabolites of the triclocarban degradation. Furthermore, total organic carbon results confirmed that the intermediates, 3, 4-dichloroaniline (4 mg L −1 ) and 4-chloroaniline (4 mg L −1 ) could be degraded up to 77% and 80% by strain YL-JM2C within 5 d. Highlights: Sphingomonas sp. strain YL-JM2C was able to degrade TCC. 3, 4-DCA, 4-CA and 4-CC are the main metabolites of TCC biodegradation. Sphingomonas sp. strain YL-JM2C was able to degrade 3, 4-DCA and 4-CA.